EFFECTIVE STRATEGIES IN OVERCOMING EDUCATION GAPS - Rinda Riztya; Ahmad Khanali; Sofia Fitri Rahmani (Adisam Publisher, 2025)
Education inequality is a major challenge that hinders socio-economic development and justice in many parts of the world. This article explores effective strategies for addressing educational disparities with a comprehensive and sustainable approach. By increasing the capacity and distribution of teachers, adjusting the curriculum to be more inclusive and relevant, as well as a strong monitoring and evaluation system, a more just and equitable educational environment can be created. Continuous training of teachers as well as providing adequate incentives play an important role in ensuring access to quality education for all children, regardless of their socio-economic background. Curricula tailored to local needs increase student engagement and the relevance of education to their communities. Additionally, continuous monitoring and evaluation is a critical tool for assessing policy effectiveness and enabling continuous adjustments based on field conditions. This article emphasizes the importance of collaboration between government, stakeholders and society to create a more equitable education system. With a holistic approach applied consistently, it is hoped that educational gaps can be minimized, creating greater opportunities for every child to reach their full potential.